Response Macronutrient Content of Saline-Resistant Paddy to the Saline Source Distance - Aditya Nugraha Putra; Martiana Adelyanti; Albert Fernando Sitorus; Qoid Luqmanul Hakim; Melati Julia Rahma; Istika Nita; Sudarto Sudarto; Alia Fibrianingtyas (UNIVERSITY OF LAMPUNG, 2021)
The impact of salinity on paddy production in Indonesia was pronounced with an average decline of 6.83% (2015-2019). Salinity interferes with macronutrients' absorption into plants, causing stunted growth (salinity contributed to a 42% decrease in paddy production). One solution to solve the salinity problem in paddy is to use saline varieties. There were very few studies on macronutrient content analysis in resistant varieties response to the salinity source's distance. This research conducted in Jabon Sidoarjo, Indonesia, aims to see the macronutrient response and plant growth to the saline source's distance. This research was conducted in Jabon District, Sidoarjo Regency, using two transects with a length of 2 km and 3.4 km, respectively. The distance between the research location and the salinity source was 10.65 km. The survey used a free grid to adjust paddy fields' location and the presence of resistant varieties. The results showed that the closer to the salinity source, the salinity indicators consisting of Electrical Conductivity, Sodium Adsorption Ratio, Exchangeable Sodium Percentage, and pH H2O would increase. The increase in salinity then affects the decrease in macronutrients (Nitrogen, Phosphor, and Kalium) in plants. However, tillers and leaves (length and number) were unaffected by high salinity levels in the soil.